Critical appraisal in rapid systematic reviews of COVID-19 studies: implementation of the Quality Criteria Checklist (QCC) - Daphne Duval; Nicola Pearce-Smith; Jennifer C. Palmer; Jason Kwasi Sarfo-Annin; Paul Rudd; Rachel Clark (Systematic Reviews, 2023)
Abstract In this letter, we briefly describe how we selected and implemented the quality criteria checklist (QCC) as a critical appraisal tool in rapid systematic reviews conducted to inform public health advice, guidance and policy during the COVID-19 pandemic. As these rapid reviews usually included a range of study designs, it was key to identify a single tool that would allow for reliable critical appraisal across most experimental and observational study designs and applicable to a range of topics. After carefully considering a number of existing tools, the QCC was selected as it had good interrater agreement between three reviewers (Fleiss kappa coefficient 0.639) and was found to be easy and fast to apply once familiar with the tool. The QCC consists of 10 questions, with sub-questions to specify how it should be applied to a specific study design. Four of these questions are considered as critical (on selection bias, group comparability, intervention/exposure assessment and outcome assessment) and the rating of a study (high, moderate or low methodological quality) depends on the responses to these four critical questions. Our results suggest that the QCC is an appropriate critical appraisal tool to assess experimental and observational studies within COVID-19 rapid reviews. This study was done at pace during the COVID-19 pandemic; further reliability analyses should be conducted, and more research is needed to validate the QCC across a range of public health topics.